Dithley’s Hermeneutical Interpretation on ‘Heaven and Smile’ Episode of Digital Comic ‘Banggaber’ - Hidayat, Syarip; Arimbawa, I Made Gede (Telkom University, 2023)
Digital comics spread with WebToon and social media platforms such as Instagram, like Banggaber digital comics, and digital comics are distributed on the internet via computers and mobile devices. The appeal of Banggaber Digital Comics can be seen in one frame and still conveys a strong message; the purpose of this research is to show the message. This research is qualitative in nature using Dilthey's hermeneutics with the visual art method in comics. Data on digital comics is proud on Instagram, a way to collect data that includes visual research and observation. The results show that individual experience directs from a historical and social perspective, showing from the visualization of comics has the message that this mother is an important part of one's life and also that past experiences can present acceptance that mothers are figures who provide peace and hope.